Process engineering studies on gold nanoparticle formation via dynamic spectroscopic approach - Chakraborty, A. (Springer Verlag, 2016)
The present paper reports a systematic study on kinetics of formation of metal nanoparticles from their precursors. Synthesis of gold nanoparticles (AuNPs) from chloroauric acid by the Turkevich method was selected as a model reaction where trisodium citrate acted as a reducing agent and stabilizer. Time-variant concentration of chloroauric acid was measured directly by monitoring UV spectroscopic absorbance at 212.5Â nm and cross-checked by iodometric titration method. The reaction was suitably modeled by pseudo-first-order kinetics, and rate constant value kÂ =Â (7.93Â Â±Â 0.67)Â ÃÂ 10â3Â sâ1 at a fixed baseline condition was reported. Morphological studies on particle growth mechanism were done by atomic force microscopy (AFM). Effects of process variablesâinitial molar ratio of reactants (0.37â5.21), temperature (333â373Â K), and pH (3.6â6.5)âon kinetic parameters were investigated. Fastest reaction rate and spherical particle symmetry were observed at an optimal reductant to precursor ratio of 1.33. From an Arrhenius plot of rate constant data, preexponential factor (AÂ =Â 8.013Â Â±Â 0.896Â mMÂ sâ1) and activation energy (EaÂ =Â 21.69Â Â±Â 2.3Â kJÂ molâ1) were calculated. A global kinetic equation for AuNP synthesis has been determined. Process conditions for synthesis of mature AuNPs with optical and morphological characteristics suitable for biomedical applications were identified. Â© 2016, Springer International Publishing Switzerland.